Efficient and mechanically-robust organic solar cells based on vertical stratification modulation through sequential blade-coating. (15th June 2022) - Zhu, Qinglian; Xue, Jingwei; Lu, Guanyu; Lin, Baojun; Naveed, Hafiz Bilal; Bi, Zhaozhao; Lu, Guanghao; Ma, Wei
Abstract: Mechanically durable organic solar cells (OSCs) with high efficiency are deemed as the ideal candidate for the power source of the next generation wearable electronic devices. However, the brittle nature of small molecules in most high-efficiency OSCs consisting of polymer and small molecule encourages easy formation of cracks in the photoactive film under deformation. Here, the vertical composition distribution of the active layer has been well optimized through sequential blade coating to realize highly deformable while efficient OSC. The optimized morphology exhibits distinct donor-rich and homogenous region distributed along the vertical direction in the bulk. The donor-rich region provides sufficient chain entanglements and strong interfaces beneficial for mechanical robustness of film, while homogeneously mixed region offers continuous interpenetrating network to maintain high device through-put, resulting in superior efficiency of 14.4% with high crack-onset strain (COS) of 30.5%. This efficiency versus COS combination is much higher than the best combination reported in all polymer systems (COS of 15.9% and efficiency of 11.1%). To the best of our knowledge, it is the highest COS value achieved in polymer-small molecule systems. The rational control over vertical stratification demonstrated here would guide researchers in the development of innovative wearable electronics. Graphical Abstract: A mechanically robust and high-performance organic solar cell with efficiency of 14.4% and crack-onset strain (COS) of 30.5% is fabricated by sequential blade coating-based strategy to modulate the vertical phase distribution, and the universality of this strategy has been verified in another high-performance system. ga1 Highlights: Organic solar cells (OSCs) with high efficiency of 14.4% and crack-onset strain (COS) of 30.5% were fabricated. High donor:acceptor ratio along the vertical direction obtained by sequential blade casting (SBC) benefits the deformability. SBC exhibits its universality in realizing mechanical robust and highly efficient OSCs. 30.5% is the highest COS value reported in OSCs with efficiency over 10%.